Jakob Sumardjo: Pelacakan Hermeneutis Historis terhadap Artefak-Artefak Kebudayaan Indonesia - Masmedia Pinem (Jurnal Lektur Keagamaan, 2013)
The cultural development in Indonesia nowadays, historically, is the blend of different multicultures. There are waves of “outside” influence shaping the Indonesian cultural characteristics. However, the outer influences do not significantly eliminate the specific values owned by the local culture. This study also tries to portray the figure of Jacob Soemarjo--one of the pioneers of the study of philosophy and culture in Indonesia. Accordingly, in its development, the old Indonesian philosophy was radically different from the new one whether in the ontological, epistemological and axiological aspect. Keywords: Indonesian Culture, Philosophy